2008
DOI: 10.1210/jc.2007-2389
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dysfunctional LHX4 Mutation with High Phenotypical Variability in Patients with Hypopituitarism

Abstract: The present report describes three new exonic LHX4 allelic variants with at least one being responsible for congenital hypopituitarism. It also extends the phenotypical heterogeneity associated with LHX4 mutations, which includes variable anterior pituitary hormone deficits, as well as pituitary and extrapituitary abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 31 publications
3
47
0
3
Order By: Relevance
“…Concerning the two variants of unknown significance, whereas Gly to Ser amino acid substitution was not predicted to have significant physico-chemical effects, Thr90Met amino acid substitution affects the LIM domain and is likely associated with important physico-chemical changes. In our in vitro studies, these variants did not modify the DNA-binding and transactivation properties of the protein (17). Considering the limitations of functional studies, however, it cannot be ruled out that these variants may somehow be functionally relevant.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Concerning the two variants of unknown significance, whereas Gly to Ser amino acid substitution was not predicted to have significant physico-chemical effects, Thr90Met amino acid substitution affects the LIM domain and is likely associated with important physico-chemical changes. In our in vitro studies, these variants did not modify the DNA-binding and transactivation properties of the protein (17). Considering the limitations of functional studies, however, it cannot be ruled out that these variants may somehow be functionally relevant.…”
Section: Discussionmentioning
confidence: 53%
“…We also identified two LHX4 variants (c.1108GOA heterozygote, p.Gly370Ser and c.296 COT heterozygote, p.Thr90Met), with normal DNA-binding and transactivation properties in transfection studies as we reported (17). Moreover, 56.3% of patients presented the c.983GOA (p.Asn328Ser) LHX4 polymorphism in a heterozygous (40%) or homozygous (16.3%) way.…”
Section: Molecular Analysesmentioning
confidence: 51%
See 2 more Smart Citations
“…There is commercial testing available for both POU1F1 and PROP1, and research testing available at many academic institutions. Pediatric endocrinologists who treat patients with combined pituitary hormone deficiencies should strongly consider offering genetic testing, as the expanding reports of mutations may offer relevant clinical information.Mutations in the transcription factor LHX4 can be inherited in an autosomal fashion and result in variable anterior pituitary hormone deficiencies and preserved fertility (32,33). Endocrinologists who treat adult patients with idiopathic congenital hypopituitarism should also present the option of genetic testing to their patients, even in individuals in whom genetic mutations were not previously found, as novel mutations continue to be discovered.…”
mentioning
confidence: 99%